2017
DOI: 10.1051/e3sconf/20171901037
|View full text |Cite
|
Sign up to set email alerts
|

Settlement of reactive power compensation in the light of white certificates

Abstract: Abstract. The article discusses the problem of the determination of savings on active energy as a result of a reactive power compensation. Statutory guidance on the required energy audit to obtain white certificates in the European Union was followed. The analysis was made on the basis of the Polish Law. The paper presents a detailed analytical method and an estimation method taking into account the impact on the line, the transformer and the generator. According to the relevant guidelines in the European Unio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…As part of the configuration, the following are defined: the type of state logic and the range of their intervals; options for visual presentation in the state table; and RBF network parameters. The object states accepted for multi-valued logic were defined in Polish standards concerning the reliability and quality of service [6,[33][34][35][36][37][38][39] (Figures 8 and 9). Therefore, the classification stage in the diagnosis process determines a specific state for each basic element of the technical object examined.…”
Section: Research and Analysis Of Multi-valued Diagnoses Developed By The Diag 2 System For Devices Of The Electric Hybrid Power System Fmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of the configuration, the following are defined: the type of state logic and the range of their intervals; options for visual presentation in the state table; and RBF network parameters. The object states accepted for multi-valued logic were defined in Polish standards concerning the reliability and quality of service [6,[33][34][35][36][37][38][39] (Figures 8 and 9). Therefore, the classification stage in the diagnosis process determines a specific state for each basic element of the technical object examined.…”
Section: Research and Analysis Of Multi-valued Diagnoses Developed By The Diag 2 System For Devices Of The Electric Hybrid Power System Fmentioning
confidence: 99%
“…At present, electric power systems using renewable energy (wind, solar etc.) are developing particularly intensively; this can be seen as regards the subject of publications [29][30][31][32][33][34][35][36][37][38]. A novelty in this article in the aspect of electric power supply systems is a presentation of the method of building and developing diagnostic knowledge bases for electric hybrid power supply systems for the HoW.…”
Section: Introductionmentioning
confidence: 99%
“…In the research [28], population growth was found to be the largest driver of energy consumption and air pollutant emissions from 1997-2010. Investments that reduce the production of electricity, which reduces the negative impact on the environment is one of activities [29]. Air emission pollutant prediction has attracted special legislative and scientific attention due to the harmful effects on human health.…”
Section: Emissions Of Pollutants In Polandmentioning
confidence: 99%
“…In addition to activities performed in the production and receiving area, the distribution area is also an important element. An important factor here is to take care of the appropriate reduction in the current value flowing in the power system [1]. The key tools for understanding the phenomena that cause increased current flow in an electrical circuit are mathematical methods of describing the flow of energy.…”
Section: Introductionmentioning
confidence: 99%